Store Ambience on Young Apparel Consumers’ Impulsive Buying Behaviour (American Journal of Interdisciplinary Research and Innovation, 2024)
This research aimed to discern the influence of store ambiance on the impulsive purchasing behavior of consumers in the apparel sector. The study investigated the impact of various factors, namely window display (WD), promotional offers (PO), store layout (SL), background music (BM), and fragrance of the store (FOS), on consumer impulsive buying behaviour (IBB). The research was conducted involving 252 youth participants. A questionnaire, developed from existing literature, served as the primary data collection tool. The gathered data underwent analysis through correlation tests and linear regression. The research findings underscore the significance of certain store features, specifically window display, promotional offers, and fragrance, in influencing consumer impulsive purchase behaviour within the apparel sector. Consequently, the study provides practical recommendations for retailers to enhance the overall ambience of their stores to stimulate impulsive buying among apparel consumers.